2008
DOI: 10.1590/s1516-89132008000700032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of splenectomy on the biodistribution of technetium-99m dimercaptosuccinic acid (99mTc-DMSA) in rats

Abstract: (88.8 ± 18.6 mg/dL) and creatinine (0.56 ± 0.08 mg/dL), compared to the controls (51.5±1.6, 0.37±0.02mg/dL, respectively), as well as increase in platelets and leucocytes, and hematocrit reduction. The analysis of the results indicates that in rats, splenectomy seems to alter the renal function and the uptake of 99mTc-DMSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Study described by Açucena et al 18 showed that splenectomy in rats altered renal function and uptake of 99m Tc-DMSA. Stokland et al 9 showed that decreased uptake of 99m…”
Section: Organsmentioning
confidence: 95%
“…Study described by Açucena et al 18 showed that splenectomy in rats altered renal function and uptake of 99m Tc-DMSA. Stokland et al 9 showed that decreased uptake of 99m…”
Section: Organsmentioning
confidence: 95%